Integration of Next-Generation Sequencing to Treat Acute Lymphoblastic Leukemia with Targetable Lesions: The St. Jude Children’s Research Hospital Approach - Inaba, Hiroto; Azzato, Elizabeth M.; Mullighan, Charles G. (Frontiers in Pediatrics, 2017)
Acute lymphoblastic leukemia (ALL) is the most common type of cancer in children. In recent Total Therapy studies conducted at St. Jude Children’s Research Hospital, children with ALL had a 5-year overall survival of around 94%. This is the result of a combination of risk stratification based on the biological features of the leukemic cells and the response to treatment (as assessed by the detection of minimal residual disease), treatment modification based on pharmacodynamic and pharmacogenomic data, and improved supportive care. However, innovative approaches are required to further improve survival to as close to 100% as possible and to reduce the adverse effects of treatment. Next-generation sequencing of leukemic cell DNA and RNA, as well as of germline DNA, can identify submicroscopic genetic structural changes and sequence alterations that contribute to leukemogenesis. Next-generation sequencing data can be used to define new ALL subtypes, to help improve treatment response and reduce adverse effects, and to identify novel prognostic markers and therapeutic targets to facilitate personalized precision medicine. In this article, we describe our approach to detecting targetable lesions in patients with ALL by next-generation sequencing and explain how we integrate the sequencing data into the treatment of these patients.